Postcolonial Discourse Reflected Through Magical Realism in Tess Uriza Holthe’s When the Elephants Dance - Gabriella Immanuel Ndoen; Mike Wijaya Saragih (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This article aims to show the postcolonial discourse of the Philippines through the utilization of magical realism in the novel When the Elephants Dance (2002) by Tess Uriza Holthe. When the Elephants Dance is intrinsically structured into four main sections which describe the events leading up to Japan’s surrender. Inside these four sections, the story is integrated with five sub-stories from accompanying characters which are A Cure for Happiness, Mang Minno, Ghost Children, The Twilight People, and The Portrait of an Aristocrat. These sub-stories act as one of the highlights of the novel since they are utilized by the characters as a way to retain their sanity and cope with the tragic experiences of living in the middle of a war. The characters’ coping mechanism of telling their life stories that are filled with Filipino mythology reflects the postcolonial discourse of the Philippines prior to and during World War II. With the research limitation of analyzing the story of Mang Minno, this research will use the theory of magical realism by Wendy B. Faris to see the presence of magical realism, as well as the utilization of New Historicism as a bridge to analyze the postcolonial discourse. The results show that by integrating magical realism and history, Holthe was successful in depicting historical events that occurred in the Philippines under the fictional aspect of the novel. Holthe used magical realism to conceal the postcolonial discourse of alterity and emphasize the magnificence of Catholicism in the Philippines.